Teaterpubliken i svensk kulturpolitik - Hoogland, Rikard (Peripeti, 2009)
The Swedish cultural policy has since the 1930’s been engaged in distributing art on a professional level to all citizens and for its fulfilling reduced all hindrances. This article aims to analyze the way the theatre audience has been discussed in governmental cultural policy reports since 1933 years theatre report. In focus stands the failure to fulfill the goal that the theatre audience should be a cross-section of the Swedish society (social, ethnic, gender).